(untitled) (IASH Indian Journal of Arid Horticulture, 2026)
Jodhpur Jeera-1 (MCU-105) is a newly developed high-yielding cumin (Cuminum cyminum L.) variety developed through pure line selection from a local germplasm collection (GP-205) at Dr. B.R. Choudhary Agricultural Research Station, Mandor, Agriculture University Jodhpur, Rajasthan. The variety was evaluated under the AICRP on Spices at five locations across Rajasthan and Gujarat for three consecutive years (2021-22 to 2023-24). In multi-location coordinated trials, Jodhpur Jeera-1 recorded a weighted mean seed yield of 566 kg/ ha, registering a 22.8% yield advantage over the national check variety GC-4 (469 kg/ ha). The variety possesses a superior essential oil content of 4.34%, which is 3.6% higher than that of GC-4 and is characterized by a tall, erect plant type with abundant branching and compact umbels. It matures in 118–138 days, placing it in the medium maturity group. Under natural field conditions, Jodhpur Jeera-1 exhibits moderate resistance to both Fusarium wilt and Alternaria blight, recording a mean blight disease incidence of 26.0% compared to 34.4% in GC-4, along with lower infestation by aphids and thrips. The variety was recommended for commercial cultivation in irrigated, timely sown rabi conditions of Rajasthan in 2025.